Ultra-broadband infrared metamaterial absorber based on MDMDM structure for optical sensing - Li, Fengjie; Du, Jiansen; Wang, Shang; Yu, Ruitao; Wang, Xi; Zhang, Tiqiang; Chi, Zongtao; Wang, Bin; Li, Ning (Frontiers in Astronomy and Space Sciences, 2024)
Infrared observation is a crucial tool in the study of astronomical celestial bodies. Metamaterials have a vast prospect for applications in the field of optics due to its unique electromagnetic tunable characteristics. In order to obtain an ultra-broadband high absorption material in infrared region, we proposed a metal-dielectric-metal-dielectric-metal (MDMDM) metamaterial absorber using a titanium (Ti) nano-cross layer based on surface plasmon polariton (SPP) resonance and magnetic resonance cavity principles. The geometrical parameters of each layer have been examined carefully. The influence of incident angle from 0° to 60° is investigated for transverse electric and transverse magnetic plane-waves. Near-perfect absorption performance is achieved from near-infrared to mid-infrared region. The average absorption reaches as high as 97.49% from 2.05 μm to 6.08 μm. The absorber exhibits polarization-sensitive characteristics. The absorption peaks are 99.50% and 99.80% at 2.55 μm and 5.24 μm, respectively. The proposed material has potential applications in astronomical imaging, volcano and fire detection, remote sensing, biological monitoring, and other optical devices.